Enantioselective CO2 Fixation Via a Heck‐Coupling/Carboxylation Cascade Catalyzed by Nickel. Issue 28 (22nd April 2021) - Cerveri, Alessandro; Giovanelli, Riccardo; Sella, Davide; Pedrazzani, Riccardo; Monari, Magda; Nieto Faza, Olalla; López, Carlos Silva; Bandini, Marco
Abstract: A novel asymmetric nickel‐based procedure has been developed in which CO2 fixation is achieved as a second step of a truncated Heck coupling. For this, a new chiral ligand has been prepared and shown to achieve enantiomeric excesses up to 99 %. The overall process efficiently furnishes chiral 2, 3‐dihydrobenzofuran‐3‐ylacetic acids, an important class of bioactive products, from easy to prepare starting materials. A combined experimental and computational effort revealed the key steps of the catalytic cycle and suggested the unexpected participation of Ni(I) species in the coupling event. Abstract : COTWO task . An enantioselective nickel catalyzed tandem Heck coupling/carboxylation synthetic sequence with CO2 is reported that provides ready access to 2, 3‐dihydrobenzofuran‐3‐ylacetic acids and analogous compounds ( ee up to 99 %). Labelling experiments, DFT analysis and X‐ray characterizations enabled both mechanistic steps and stereodiscriminating transition states to be fully elucidated.